Strong Coupling of Shoot Assimilation and Soil Respiration during Drought and Recovery Periods in Beech As Indicated by Natural Abundance δ13C Measurements - Blessing, Carola H.; Barthel, Matti; Gentsch, Lydia; Buchmann, Nina (Frontiers in Plant Science, 2016)
Drought down-regulates above- and belowground carbon fluxes, however, the resilience of trees to drought will also depend on the speed and magnitude of recovery of these above- and belowground fluxes after re-wetting. Carbon isotope composition of above- and belowground carbon fluxes at natural abundance provides a methodological approach to study the coupling between photosynthesis and soil respiration under conditions (such as drought) that influence photosynthetic carbon isotope discrimination. In turn, the direct supply of root respiration with recent photoassimilates will impact on the carbon isotope composition of soil-respired CO2. We independently measured shoot and soil CO2 fluxes of beech saplings (Fagus sylvatica L.) and their respective δ13C continuously with laser spectroscopy at natural abundance. We quantified the speed of recovery of drought stressed trees after re-watering and traced photosynthetic carbon isotope signal in the carbon isotope composition of soil-respired CO2. Stomatal conductance responded strongly to the moderate drought (-65%), induced by reduced soil moisture content as well as increased vapor pressure deficit. Simultaneously, carbon isotope discrimination decreased by 8‰, which in turn caused a significant increase in δ13C of recent metabolites (1.5-2.5‰) and in δ13C of soil respiration (1-1.5‰). Generally, shoot and soil CO2 fluxes and their δ13C were in alignment during drought and subsequent stress release, clearly demonstrating a permanent dependence of root respiration on recently fixed photoassimilates, rather than on older reserves. After re-watering, the drought signal persisted longer in δ13C of the water soluble fraction that integrates multiple metabolites (soluble sugars, amino acids, organic acids) than in the neutral fraction which represents most recently assimilated sugars or in the δ13C of soil respiration. Nevertheless, full recovery of all aboveground physiological variables was reached within four days –and within seven days for soil respiration – indicating high resilience of (young) beech against moderate drought.